2012
DOI: 10.1002/jmr.2176
|View full text |Cite
|
Sign up to set email alerts
|

Myelinating and demyelinating phenotype of Trembler‐J mouse (a model of Charcot–Marie–Tooth human disease) analyzed by atomic force microscopy and confocal microscopy

Abstract: The accumulation of misfolded proteins is associated with various neurodegenerative conditions. Mutations in PMP-22 are associated with the human peripheral neuropathy, Charcot-Marie-Tooth Type 1A (CMT1A). PMP-22 is a short-lived 22 kDa glycoprotein, which plays a key role in the maintenance of myelin structure and compaction, highly expressed by Schwann cells. It forms aggregates when the proteasome is inhibited or the protein is mutated. This study reports the application of atomic force microscopy (AFM) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…We chose PMP22 to test our hypothesis as it is one of the abundant proteins (2–5%) in peripheral myelin [11]. Moreover, PMP22 has been found as a key player in multiple Charcot Marie Tooth Disease 1a neuropathies and has been reported to be mutated and aggregated in several neuropathies [32], [33], [34], [35]. We first asked whether the primary sequence of PMP22 can predict and identify any domain that have motif(s) of hydrophobicity as hydrophobic domains in general initiate the aggregation process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose PMP22 to test our hypothesis as it is one of the abundant proteins (2–5%) in peripheral myelin [11]. Moreover, PMP22 has been found as a key player in multiple Charcot Marie Tooth Disease 1a neuropathies and has been reported to be mutated and aggregated in several neuropathies [32], [33], [34], [35]. We first asked whether the primary sequence of PMP22 can predict and identify any domain that have motif(s) of hydrophobicity as hydrophobic domains in general initiate the aggregation process.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are important considering that the diabetic nerve morphology after necropsy has similar opaqueness to that of sciatic nerves isolated from J trembler mice, a model of CMT1a (PMP22 mutant mice, a model of Hereditary Neuropathy with Liability to Pressure Palsy). In this context, it is also interesting to note that an increase in PMP22 insolubility in J trembler mice is causal for the demyelination phenotype [32], [33], [34], [35]. Moreover, a chromosome 22 duplication in humans containing the PMP22 protein increases PMP22 insolubility in mice and reduces PMP22 incorporation in myelin while heat shock improves myelin incorporation [34], [35], [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data showed that under identical isometric loads, the nerves of CTS patients tended to be less deformable than the nerves of normal subjects. Certain pathological conditions such as diabetes, 4 Charcot–Marie–Tooth disorder, 19 and glaucoma 18 have been shown to cause substantial increases in nerve stiffness. Therefore, one plausible explanation for less localized deformation in the CTS patients is that the nerve, and/or the subsynovial connective tissue surrounding the nerve is mechanically stiffer than in normal subjects, and thus does not deform as dramatically at locations of direct interaction with neighboring structures.…”
Section: Discussionmentioning
confidence: 99%
“…Type IV collagen was found to accumulate with PMP22 protein in the perinuclear region of TrJ Schwann cells. Fixed nerve fibers from TrJ mice were softer and smoother than wild-type fibers by using atomic force microscopy (Rosso et al, 2012). The disruption of F-actin cytoskeletal organization in TrJ nerve fibers has also been documented (Kun et al, 2012), which has led to the idea that PMP22 point mutations could potentially affect protein secretory pathways of extracellular matrix components (Rosso et al, 2012).…”
Section: Mutations In the Pmp22 Gene And Their Related Diseasesmentioning
confidence: 99%